IMPLEMENTASI SISTEM MUTU INTERNAL UNTUK MENINGKATKAN MUTU PENDIDIKAN DASAR - Abdullah, Dede; Pasaribu, Rhendivan; Ninda A, Anggistia; Dominico P S, Claudi (Manajemen Pendidikan, 2023)
To implement state education goals, internal quality assurance is carried out in relation to national education standards. Internal quality is now applied not only to higher education, but also to primary and secondary education. We continue to ensure and lead educational quality assurance and compliance in primary and secondary school units. The aim of this research is to determine and describe the implementation of the internal quality system cycle. The techniques used in data collection are: Observation, interviews, documentary research. The results of the research show that the quality improvement steps implemented at Bawamai Pontianak Elementary School are in accordance with the SPMI cycle steps including: First, school self-evaluation based on education quality certificates; second, a plan to improve quality through the formation of a quality committee and analysis of the results of the Kermbali School self-evaluation; Implementation of quality improvement, fourth, evaluation of follow-up and results of quality improvement after quality improvement, and fifth, return to next year's quality plan. The results of implementing internal quality assurance influence a more innovative learning process, student and school performance, satisfaction and success of internal and external customers. Eight national education standards.